2009
DOI: 10.1074/jbc.m109.008748
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone Stimulates Elastogenesis in Cardiac Fibroblasts via Mineralocorticoid Receptor-independent Action Involving the Consecutive Activation of Gα13, c-Src, the Insulin-like Growth Factor-I Receptor, and Phosphatidylinositol 3-Kinase/Akt

Abstract: We previously demonstrated that aldosterone, which stimulates collagen production through the mineralocorticoid receptor (MR)-dependent pathway, also induces elastogenesis via a parallel MR-independent mechanism involving insulin-like growth factor-I receptor (IGF-IR) signaling. The present study provides a more detailed explanation of this signaling pathway. Our data demonstrate that small interfering RNA-driven elimination of MR in cardiac fibroblasts does not inhibit aldosterone-induced IGF-IR phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 75 publications
2
30
0
3
Order By: Relevance
“…It has been well documented that the persistent excessive actions of aldosterone, commonly by a combination of salt loading, cause adverse cardiovascular effects primarily via MR-dependent pathways (Matsui et al 2008. On the other hand, ourselves and others have recently reported that aldosterone exerts transient but favorable effects on cardiocytes in vitro, mainly via rapid MR-independent actions (Yamamuro et al 2006, Bunda et al 2009, Nagoshi et al 2012. In agreement with these findings, the present ex vivo study demonstrated the rapid, favorable effects of aldosterone on cardiac functional recovery and injury during ischemia-reperfusion, although aldosterone did not affect the baseline cardiac function (Table 1), congruent with the findings of previous reports by other groups (Fujita et al 2005, Matsui et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that the persistent excessive actions of aldosterone, commonly by a combination of salt loading, cause adverse cardiovascular effects primarily via MR-dependent pathways (Matsui et al 2008. On the other hand, ourselves and others have recently reported that aldosterone exerts transient but favorable effects on cardiocytes in vitro, mainly via rapid MR-independent actions (Yamamuro et al 2006, Bunda et al 2009, Nagoshi et al 2012. In agreement with these findings, the present ex vivo study demonstrated the rapid, favorable effects of aldosterone on cardiac functional recovery and injury during ischemia-reperfusion, although aldosterone did not affect the baseline cardiac function (Table 1), congruent with the findings of previous reports by other groups (Fujita et al 2005, Matsui et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This effect of Gal-3 on aldosterone actions was confirmed in human cardiac fibroblasts where aldosterone and Gal-3 showed proinflammatory and profibrotic properties in cardiac fibroblasts, increasing inflammatory markers, MMP activities, and ECM components, as it has been previously published in other cell types. 19,25 Moreover, in cardiac fibroblasts, Gal-3 silencing was able to prevent the increase in inflammatory and fibrotic markers induced by aldosterone.…”
Section: Discussionmentioning
confidence: 99%
“…1995), fibroblasts (Bunda et al. 2009), vascular smooth muscle cells (Jaffe and Mendelsohn 2005), endothelial cells (EC) (Caprio et al. 2008), and infiltrated immune cells (Bene et al.…”
Section: Introductionmentioning
confidence: 99%